Environmental policy an economic perspective - Walker, Thomas (Thomas J.); Sprung-Much, Northrop 1991-; Goubran, Sherif 1991- (Wiley-Blackwell, 2020)
"Global environmental challenges have caused a range of policy solutions, approaches, and models to emerge. As these challenges are expected to intensify in the near future, environmental policy and its instruments are increasingly becoming a topic of discussion, action, and disagreement in academic, professional, and mass media outlets. This fixation on the topic of policy is well-justified considering the consequences policy can have on all levels of society - global, national, sectoral, organizational, and even personal. Policy has a vital role in reducing environmental damage, incentivizing positive environmental behavior, and guiding practice toward a more sustainable future. While most policies have economic repercussions, environmental policies, and specifically new environmental policy instruments, have exhibited a special and complex relation to the economy. The environment can thus be considered an envelope encompassing and sustaining the economic system - much more than just a factor of production"--